Metabolomics and transcriptomics analyses provide new insights into the nutritional quality during the endosperm development of different ploidy rice - Xian, Lin; Tian, Jiaqi; Long, Yanxi; Ma, Huijin; Tian, Min; Liu, Xiangdong; Yin, Guoying; Wang, Lan (Frontiers in Plant Science, 2023)
Autotetraploid rice is developed from diploid rice by doubling the chromosomes, leading to higher nutritional quality. Nevertheless, there is little information about the abundances of different metabolites and their changes during endosperm development in autotetraploid rice. In this research, two different kinds of rice, autotetraploid rice (AJNT-4x) and diploid rice (AJNT-2x), were subjected to experiments at various time points during endosperm development. A total of 422 differential metabolites, were identified by applying a widely used metabolomics technique based on LC-MS/MS. KEGG classification and enrichment analysis showed the differences in metabolites were primarily related to biosynthesis of secondary metabolites, microbial metabolism in diverse environments, biosynthesis of cofactors, and so on. Twenty common differential metabolites were found at three developmental stages of 10, 15 and 20 DAFs, which were considered the key metabolites. To identify the regulatory genes of metabolites, the experimental material was subjected to transcriptome sequencing. The DEGs were mainly enriched in starch and sucrose metabolism at 10 DAF, and in ribosome and biosynthesis of amino acids at 15 DAF, and in biosynthesis of secondary metabolites at 20 DAF. The numbers of enriched pathways and the DEGs gradually increased with endosperm development of rice. The related metabolic pathways of rice nutritional quality are cysteine and methionine metabolism, tryptophan metabolism, lysine biosynthesis and histidine metabolism, and so on. The expression level of the genes regulating lysine content was higher in AJNT-4x than in AJNT-2x. By applying CRISPR/Cas9 gene-editing technology, we identified two novel genes, OsLC4 and OsLC3, negatively regulated lysine content. These findings offer novel insight into dynamic metabolites and genes expression variations during endosperm development of different ploidy rice, which will aid in the creation of rice varieties with better grain nutritional quality.